2013
DOI: 10.1007/s12098-013-1044-5
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic West Syndrome Secondary to Glucose Transporter-1(GLUT1) Deficiency with Complete Response to 4:1 Ketogenic Diet

Abstract: Glucose transporter type 1 (GLUT-1) deficiency is a rare cause of preventable intellectual disability. Intellectual disability is due to refractory seizures in infancy and reduced supply of glucose to the brain. The authors report a third born male child of consanguineous parentage who presented with infantile spasms. Initially, he had refractory convulsions of focal, generalised, and myoclonic jerks, not responding to multiple anticonvulsants. He also had choreoathetoid movements. On examination he had microc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…Moreover, there are certainly patients (e.g. GLUT1 transporter deficiency) for whom the ketogenic diet should be administered first-line [35]. We have only shown that the ketogenic diet is reasonably welltolerated and of limited efficacy among our highly-refractory cohort.…”
Section: Demographicsmentioning
confidence: 76%
“…Moreover, there are certainly patients (e.g. GLUT1 transporter deficiency) for whom the ketogenic diet should be administered first-line [35]. We have only shown that the ketogenic diet is reasonably welltolerated and of limited efficacy among our highly-refractory cohort.…”
Section: Demographicsmentioning
confidence: 76%
“…In previous report, a patient with infantile spasms who did not respond to several antiepileptic drugs diagnosed as GLUT-1 deficiency. He was treated with ketogenic diet and later the seizure stopped11). These observations suggest that earlier detection of GLUT-1 in infantile spasms protects patients from disease progression.…”
Section: Discussionmentioning
confidence: 93%
“…Various seizure types may occur, including generalized tonic or clonic, atypical absences, atonic, myoclonic, myoclonic astatic, or focal. GLUT1 deficiency syndrome has rarely been reported in IS patients who responded to the ketogenic diet fully or partially, including a patient with a missense mutation in SLC2A1 (Table ).…”
Section: Metabolic Errors In Organic Moleculesmentioning
confidence: 99%